Structure Modification of Quinine on C-9 Hydroxyl Group via Esteriﬁcation Reaction - Teni Ernawati; Minarti Minarti; Puspa Dewi Narrij Lotulung (Chemistry Department, The University of Brawijaya, 2020)
Concept the role played by modified quinine in the asymmetric hydroxyl group inspired studies of modified quinine as chiral organic that lead to drug discovery development. A simple and efficient method for C-9 alkylation and arylation of quinine derivatives was reported. Series quinine derivatives were synthesized through the esterification of the hydroxyl group of quinine. The reaction with various alkyl and aryl carbonyl chloride resulted in the series of ester quinine derivatives. The structure of quinine derivatives was characterized by IR, melting point, UV, 1H NMR, 13C NMR, LCMS.